The human right to language : communication access for deaf children - Siegel, Lawrence M., 1946- (Book collections on Project MUSE., 2008)
"In 1982, the United States Supreme Court ruled that Amy Rowley, a deaf six-year-old, was not entitled to have a sign language interpreter in her public school classroom. Lawrence M. Siegel wholeheartedly disagrees with this decision in these pages. Instead, he contends that the United States Constitution should protect every deaf and hard of hearing child's right to communication and language as part of an individual's right to liberty. Siegel argues that when a deaf or hard of hearing child sits alone in a crowded classroom and is unable to access the rich and varied communication about her, the child is denied any chance of success in life."--Jacket.